Research on the “Privacy Paradox” behaviors of online users from the perspective of attitude ambivalence: ERPs evidence - Qiuhua Zhu; Rui Sun; Dong Lv; Yiyang Shen; Shukun Qin (PLoS ONE, 2025)
The “privacy paradox” phenomenon and its explanations are becoming impediments to the correct identification of user privacy attitudes, and understanding the link between privacy attitude instability and behavior helps enterprises to correctly interpret user privacy needs, ensuring the long-term and steady growth of digital businesses. Grounded in the bounded theory of limited cognitive resources and associative-propositional evaluation model (APE model), this research employs ERP technology, targeting the instability of individual attitudes, the study introduces the usefulness of recommendation information and the intrusiveness of recommendation information, privacy intrusiveness and information interestingness, recommendation usefulness and information aversion as experimental stimulus variables of attitude ambivalence, and explores the internal cognitive mechanism of user privacy attitude ambivalence and disclosure behavior. The results show: (1) Under conditions of high intrusiveness of recommendation information, users are more prone to disclose privacy if the recommendation is viewed as highly useful compared to when it is less useful; there is no noteworthy disparity in privacy disclosure under conditions of low informational intrusiveness. (2) Relative to conditions of both high informational intrusiveness with low usefulness, and low privacy intrusiveness combined with low information interestingness, users manifest a higher propensity for privacy disclosure under the circumstances of low privacy invasiveness with highly information interestingness, and high recommendation usefulness along with high information aversion, prompting reduced amplitudes in P2 and N2 waves. Moreover, a larger P2 wave amplitude is evoked when there is lower perceived usefulness in recommendations coupled with less information aversion, as contrasted with higher perceived usefulness and higher aversion. This study examines the cognitive mechanism between privacy attitude ambivalence and disclosure conduct, presenting a fresh perspective for research on the “privacy paradox”, enabling businesses to deeply grasp the instability of user attitudes in conjunction with behavioral responses, significantly contributing to better protection of user privacy and the improvement of the user experience.